PENGARUH LIFESTYLE DAN IN STORE PROMOTION TERHADAP IMPULSE BUYING (STUDI PADA KONSUMEN MATAHARI DEPARTEMENT STORE JAVA MALL SEMARANG) - Alinda Mahdiyan; Agus Hermani (Jurnal Ilmu Administrasi Bisnis, 2019)
Matahari Department Store is one of the modern retailers providing various fashion products for middle-class consumers. MDS Java Mall Semarang in the past three years there was fluctuation in sales. This study aimed to determine the influence of Lifestyle consumers and in store promotion on impulse buying in MDS Java Mall. The type of research was explanatory research and the total sample is 100 respondents. The data collection used were questionnaires with Likert measurement scale. The data analysis methods used were validity and reliability test, correlation coefficient(R), regression test, determination coefficient(R2), significance of t test and F test with SPSS 21.0 application. The results showed a positive and significant influence between lifestyle and in store promotion on impulse buying for consumers of MDS Java Mall, both partially and simultaneously. The variabel of Lifestyle had the greatest influence on impulse buying which was equal to 27.5% while in store promotion was 20%. Companies need to follow the development of consumer lifestyle and provide quality, branded and complete products. In store promotion can be improved by structuring the display of products to make it more attractive and make consumers easier in choosing products and by cooperating with more banks or payment applications that provide big discounts with easier terms.